Aseptic Revision Total Knee Can Be Performed as Part of a Short-Stay Arthroplasty Program: An Analysis of the National Surgical Quality Improvement Program Database - Gu, Alex; Gerhard, Eleanor F.; Wei, Chapman; Bovonratwet, Patawut; Stake, Seth; Sculco, Peter K.; McLawhorn, Alexander S. (The Journal of Knee Surgery, 2019)
Total knee arthroplasty (TKA) is becoming an increasingly common procedure to alleviate knee pain often associated with osteoarthritis. As the number of revision TKAs performed continues to increase, there remains a debate regarding the efficacy of discharging patients earlier than the conventional 3 to 4 days in the postoperative period. A variety of studies have begun to show that interchangably discharge in the primary TKA setting has an economical benefit while causing either a reduction or no difference in patient outcomes. This study aims to determine the effect of rapid discharge at 0- to 2-day postoperative stay compared to the conventional 3- to 4-day postoperative stay on postdischarge complications in patients undergoing revision TKA. A retrospective cohort study was conducted using data collected through the American College of Surgeons National Quality Improvement Program Database. All patients who underwent aseptic revision TKA between 2005 and 2016 were identified and stratified into groups based on length of stay: 0 to 2 days versus 3 to 4 days. Patients suffering from predischarge complications were excluded to minimize bias. Single-component versus both-component revisions were analyzed. The incidence of adverse events following discharge was evaluated with univariate and logistic multivariate analyses where appropriate. Patients who underwent single-component revisions and were discharged rapidly were less likely to develop minor complications (p = 0.001; odds ratio [OR]: 0.355; 95% confidence interval [CI]: 0.188–0.671) and septic complications (p = 0.016; OR: 0.011; 95% CI: 0–0.430) within the 30-day postoperative period. No differences were observed in discharge cohorts among patients undergoing both-component revisions. We found that rapid discharge following aseptic revision TKA is not associated with increased risks for postoperative complications. Rapid discharge may have benefits for healthy patients undergoing single-component revisions. Careful selection of revision TKA patients for rapid discharge may help to lower the increasing costs of the procedure and improve patient outcomes. Further study is required to refine the selection criteria to identify patients eligible for short stay or outpatient revision TKA.
Keywords: knee; replacement; arthroplasty; postoperative; complications